Empowerment-Based Training Model (EBTM) sebagai Strategi Penguatan Kader Kesehatan Sekolah dalam Pelaksanaan Usaha Kesehatan Sekolah (UKS) di Boarding School - Pradana P.H, Firmansyah Kholiq; Iqbal, Muhammad; Setyawati, Vilda Ana Veria; Rimawati, Eti (Universitas Pahlawan Tuanku Tambusai, 2026)
School Health Programs (Usaha Kesehatan Sekolah/UKS) are a strategic component in promoting Healthy Schools, particularly in secondary boarding schools that face more complex health management challenges. A major obstacle in UKS implementation is the limited capacity of School Health Cadres (Kader Kesehatan Sekolah/KKS). This community service program aimed to enhance the knowledge and capacity of KKS through a Training of Trainers approach based on the Empowerment-Based Training Model (EBTM) at SMA Islam Sultan Agung 3 Semarang. A participatory descriptive method was employed, involving 80 participants consisting of KKS and boarding school mentors. The activities included interactive lectures, group discussions, case studies, and practical simulations covering Healthy School concepts, the Trias UKS framework, KKS roles, and standard operating procedures (SOPs). Evaluation was conducted using pre-tests and post-tests, observations, and participant feedback. The results demonstrated a significant increase in participants’ knowledge, with the high-knowledge category rising from 19% in the pre-test to 93% in the post-test, and no participants remaining in the low-knowledge category. The EBTM approach proved effective in strengthening human resource capacity for UKS and shows strong potential for sustainable implementation in boarding school settings.